تعزيز الإلزام في التشريعين الوضعي والسماوي ( دراسة تحليلية مقارنة ) - TAMER, ALEND SALAHALDIN; RASHID, IHSAN AHMED (Journal of Duhok University, 2024)
The legislative obligation constitutes a restriction on individuals and includes assigning them to do or refrain from doing work, and because human nature in general does not favor restrictions and submission, but rather prefers freedom and independence, which raises the question: How can legislative obligation interact with the conviction of individuals? Especially that relying on the abstract penalty does not guarantee the strengthening of legislative obligation and the formation of conviction among individuals of the need to respect it, and the reliance on the abstract penalty in imposing legislative obligation will make legislation a means that some philosophers tried to rely on to legitimize the absolute sovereignty of rulers and those holding power to achieve their personal interests. Therefore, it is necessary to search for means that help legislative obligation to interact with the conviction of individuals, and One of the most important of these means is justice, which consists of two elements: freedom and equality. Where the legislative obligation should achieve them in their full correct sense so that it can get individuals to obey, otherwise the legislative obligation will not find anything to help it to get individuals to obey other than the use of the penalty, which is a remedial means that does not find its role until after violating the legislative obligation.